DETERMINATION OF LEADING PLANTATION COMMODITIES OGAN KOMERING ULU DISTRICT: DETERMINATION OF LEADING PLANTATION COMMODITIES OGAN KOMERING ULU DISTRICT - Yenni Sihite; Firda Novalia; Ahmad Iskandar; Putri Ayu Ogari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2020)
This study aims to (1) determine the superior agricultural sub-sector, (2) identify leading agricultural sub-sector potential commodities to be developed as economic drivers in Ogan Komering Ulu Regency, (3) determine the pattern and structure of growth of the leading agricultural sub-sectors and commodities in Ogan Regency Komering Ulu. The method used is a purposive method. The data used are time series data, that is, secondary data of the OKU Regency GRDP at current prices (2013-2017) and data on the area of agricultural commodity production over a period of 5 years (2014-2018). The analysis shows that the estate crops sub-sector is the leading agricultural sub-sector in OKU Regency. The main agricultural commodities of the estate crops subsector are oil palm, coconut, rubber, coffee, sugar cane and pepper. The patterns of growth in agriculture and leading commodities in the Ogan Komering Ulu Regency consist of: the plantation and forestry sub-sectors as fast-growing subsectors. While the food crops sub-sector is an advanced but depressed sub-sector, while the Livestock and Fisheries sub-sector are relatively lagging. Leading commodities in the estate crops sub-sector such as oil palm, coconut and cocoa are advanced and fast developing commodities; while rubber and coffee are included in developing commodities; for sugar cane and pepper, including commodities that are relatively left behind.